EFFECTIVENESS OF BUANA.ID: CULTURE-BASED AUGMENTED REALITY LEARNING MEDIA AS A CHARACTER BUILDER FOR STUDENTS - Dwi Retnani Srinarwati; Annisa Dwi Sulistyaningtyas; Hanim Faizah; Icha Dwi Listari (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the effectiveness of BUANA.ID, a local culture-based Augmented Reality (AR) learning media, in supporting the learning process and strengthening the character of junior high school students. The study uses a quantitative descriptive approach with respondents being teachers and junior high school students who have implemented BUANA.ID in learning activities. Data collection was conducted through a satisfaction questionnaire covering aspects of ease of use, media appeal, learning usefulness, and its contribution to strengthening student character. The data were analyzed using descriptive statistics in the form of percentages and mean values. The results showed that the majority of teachers and students responded positively with a high level of satisfaction with the use of BUANA.ID. The questionnaire results showed that the effectiveness level of BUANA.ID was in the highly effective category, in terms of media appeal, ease of use, assistance in understanding teaching materials, and clear and readable BUANA.ID media content. Teachers also considered this media effective in increasing student engagement and facilitating contextual learning, while students felt that learning became more interactive, interesting, and meaningful. The integration of local cultural content in AR media has been proven to contribute to character building, such as discipline, honesty, hard work, responsibility, and mutual cooperation. Based on the results of the teacher and student satisfaction survey, it can be concluded that BUANA.ID is effective as an innovative learning medium that supports learning and character building for junior high school students.